The Distribution of the Antarctic Limpet Nacella concinna (Nacellidae) on Underwater Landscapes of the Meek Channel, Argentine Islands, Graham Land - A. E. Berezkina; M. Yu. Shrestha; O. I. Sinna; D. V. Shmyrov; A. Yu. Utevsky (Ukrainian Antarctic Journal, 2019)
Objective(s). To clarify the patterns of Nacella concinna (Nacellidae) distribution in the water area of the Argentine Islands Archipelago (Meek Channel). Methods. Morphometric, statistical, cartographic methods as well as geoinformation technologies were used. Results. Analyzed the patterns of mollusc distribution on different transects, taking into account their morphometric characteristics — the length of the shell, the mollusс weight, the population density. It is determined that the distribution of Nacella concinna subpopulations does not have any visible strict regularity. At different transects with an insignificant exception the morphometric characteristics of the mollusсs are distributed both in classical and non-classical models. At the MK1 transect is shown the classical model of the distribution of morphometric characteristics, namely with an increase in the mollusс population density, the morphometric characteristics (shell length and weight of the mollusс) tend to decrease. At the MK2 transect is shown non-classical distribution model. The morphometric characteristics (shell length, mollusс weight) increase with an increase in the population density of the molluscs. At the MK3 transect is shown the classical distribution model, but a characteristic feature is an increase in the population density up to 5 m depth and a gradual decrease in the population density from 5 to 20 m. Geoinformation models of the Nacella concinna distribution by depth in the water area of the Ukrainian Antarctic Akademik Vernadsky station were constructed. Conclusions. Maps of the distribution of the Nacella concinna population were created for this region for the first time. The dimensional classes of the Nacella concinna subpopulation from selected water areas of the Argentine Islands were described.